2017
DOI: 10.1007/s10643-017-0883-5
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Ability to Identify Children at Early Risk for Reading Difficulties in Grade 1

Abstract: The aim of the study was to investigate what kinds of assessment practices class teachers and special educational needs (SEN) teachers use in assessing first grade students' pre-reading skills (letter knowledge and phonological skills). Further, we investigated to what extent teachers were able to identify difficulties in pre-reading skills of the lowest achievers. The accuracy of teacher ratings of students' pre-reading skills was studied by comparing teacher ratings to actual test scores. The data from two F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 41 publications
4
36
1
2
Order By: Relevance
“…Similar findings on the difficulties to reliably identify at‐risk children in Finland have been recently reported in other studies using both tests and teacher reports (Virinkoski, Lerkkanen, Eklund, Holopainen, & Aro, ). However, identification accuracy may be improved with additional measures.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings on the difficulties to reliably identify at‐risk children in Finland have been recently reported in other studies using both tests and teacher reports (Virinkoski, Lerkkanen, Eklund, Holopainen, & Aro, ). However, identification accuracy may be improved with additional measures.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the reading assessment criteria and indicators, teachers claim to have little knowledge of them [77], naming explicitly only the reading speed assessment ("In reading, sometimes we even get a chronometer and a paragraph, to see how long it takes them to read it, to assess mechanical reading" [School 4]). In general, teachers assess other aspects of reading, without clearly and precisely describing applied criteria ("one day you ask them to read, and today I'm going to mark, or at times reading in public ( .…”
Section: Assessment Criteria and Indicatorsmentioning
confidence: 99%
“…The most effective support for students with RD seems to be part-time special education in small groups (i.e., Tier 2) during Grades 1 and 2 (Holopainen et al, 2018). However, recent studies (e.g., Virinkoski et al, 2017) have shown that teachers had failed to identify a number of children who, judging from their Grade 1 test scores, needed support for their reading development. This observation suggests a need for further studies.…”
Section: Learning To Read In the Norwegian And Finnish Contextsmentioning
confidence: 99%
“…Otherwise, the principal results are likely to be expectations of failure. Further, it is important to determine whether identification at such an early stage as school entry is worthwhile, given that numbers of both false positives and false negatives are likely to be substantial (see Virinkoski et al, 2017). However, considering the promising effects reported from early interventions for students at risk of RD (see e.g., Saine et al, 2011;Solheim et al, 2018), we still believe that early identification followed by intensive support is the most effective solution.…”
Section: Implications For Practicementioning
confidence: 99%